Isolation of Mycobacterium avium ssp. paratuberculosis and other non-tuberculous mycobacteria from head lymph nodes of wild ruminants and badgers in Switzerland - Lienhard, Julia; Friedel, Ute; Paganini, Claudio; Hilbe, Monika; Scherrer, Simone; Schmitt, Sarah (Frontiers in Veterinary Science, 2024)
The family Mycobacteriaceae contains over 188 species, most of which are saprophytic nontuberculous mycobacteria (NTM). In wildlife, a variety of different NTM can be found, with different reports about their pathogenic potential. A pathogenic member of NTM is Mycobacterium avium ssp. paratuberculosis (MAP), which can infect farmed and wild ruminants. It causes the economically important chronic disease paratuberculosis. Infected farm animals are considered to be the source of infection for wild animals. Wildlife on the other hand, is thought be a reservoir for certain members of the Mycobacterium tuberculosis complex (MTBC), such as M. caprae, which causes tuberculosis in cattle and red deer. Thus, Switzerland implemented a surveillance program for tuberculosis in wild animals in 2014. Here, we describe the results from mycobacterial culture of lymph node samples collected from red deer, roe deer, chamois, ibex and badgers collected within this surveillance program during the years 2020 to 2022. Overall, samples from 548 animals were checked macroscopically for tuberculosis-like lesions. 88 animals (16.1%), which either had lesions in their lymph nodes or were male and aged above five years, were investigated using mycobacterial culture. While no MTBC was detected, 25 animals (28.4%) were positive for NTM. The most often identified NTM was M. vaccae, followed by M. avium. Most animals positive for NTM did not show any macroscopic lesions. Furthermore, MAP was isolated from head lymph nodes of two male red deer. Neither of these two animals had any macroscopic lesions in their head lymph nodes or any other signs of disease. However, the shooting sites of the two animals were located in summering alpine areas of cattle, which confirms that species transmission can occur when contaminated pastures are used by different species. In agreement with other studies, the occurrence of MAP in red deer was quite low. However, so far MAP was mostly isolated from feces and intestinal lymph nodes of wild animals. This is the first detection of MAP in head lymph nodes of red deer in Switzerland.